Exploring the lexical and semantic access afforded by novice and experienced Namibian physical science teachers' talk during electricity and magnetism lessons - Muzambani, Efraim Hiamueze (Rhodes University, Faculty of Education, Department of Education)
Challenges to learners' meaning-making in the topic of electricity and magnetism contributes to underperformance in grade 10 Physical Science in Namibian schools. Teacher talk in content-based classrooms not only contributes to learners' language development (Gibbons, 2003), but also facilitates meaning-making and cumulative knowledge-building (Halliday, 1999). However, it is possible that there are differences between the classrooms talk of novice and experienced Namibian Physical Science teachers. An understanding of differences between experienced and novice Namibian science teacher talk could inform teacher training and professional development and potentially help improve learners' meaning-making in topics such as electricity and magnetism. However, no study could be found in the Namibian context which explored whether novice and experienced teacher talk afforded similar semantic and lexical access to meaning-making. This research gap provided a strong rationale for undertaking the study reported in this thesis. The study sought to investigate the extent to which novice and experienced grade 10 Namibian Physical Science teachers' classroom talk provides semantic and lexical access to learners for the topic of electricity and magnetism. The research is informed by Legitimation Code Theory (LCT) and Systemic Functional Linguistics (SFL). Research has shown that the two theories are complementary and can be used to characterize teachers' pedagogical practices (Maton, 2014). A quantitative case study methodology was followed in this study with LCT's semantic density and SFL's lexical density as analytical tools to analyze the two teachers' classroom talk. The results from a t-test for semantic density show that there is a significant difference in the means for "semantic density waving" criterion (t-value of -2.331; p-value for 2 tail test at 95% level of 0.0040) and for the "linking downward escalators or single references" criterion (t-value of 4.649; p-value for 2 tail test at 95% level of 0.001) of teacher talk by the teachers. The overall results for semantic density indicate that the experienced teacher affords better epistemological access through semantic waves than the novice teacher, whereas the novice teacher affords better epistemological access through semantic range and semantic flow. In terms of lexical density, both teachers afforded similar access, characterized by their talk veering towards the level of information density associated with written text. The study makes a methodological contribution to science education research through its characterization of novice and experienced teachers' talk in terms of semantic waves and lexical density. This study also provides empirical insight into the differences between language use by novice and experienced Namibian Physical Science teachers, which can inform the work of educational institutions, advisory and inspectorate services in the ministry of education, and school managers. Relevant Namibian stakeholders are encouraged to consider including the topics of semantic density and lexical density, in continuous professional development programmes towards improving the meaning-making affordances of science teachers' talk.
Keywords: Knowledge, Theory of; Education, Secondary Aims and objectives-- Namibia; Science-- Study and teaching (Secondary)-- Namibia; Systemic functional linguistics; Lexical density; Electricity-- Study and teaching (Secondary)-- Namibia; Magnetism-- Study and teaching (Secondary)-- Namibia